Report on the consideration of a petition by residents of Kinyona ward regarding safeguarding public interest in the use of Gituamba land in Kinyona ward of Muranga county - National Assembly (My University, 2021)
The petition by residents of Kinyona ward regarding safeguarding public interest in the use of Gituamba land in Kinyona ward of Muranga county was presented to the house through the Hon. Sabina W. M. Chege, MP on 8th september 2020.
Keywords: Kinyona ward; Gituamba land